Lexical and Grammatical Borrowings in Raji - Dhakal, Dubi Nanda (Gipan, 2022)
When languages have a relatively small number of speakers and live along with the speakers of dominant languages, there is a gradual shrinkage in their vocabulary, and grammatical patterns. This study is mainly based on the wordlist and texts initially gathered for the primary documentation of Raji in 2018. Raji presents a typical case in which 46.2 percent lexical items are borrowed from Indic languages (and mainly from Nepali). The verbs borrowed from Indic sources exhibit systematic behavior as all of them index the suffix -e to the verb roots as a technique of accommodation before other suffixes are added to them. Some lexical items end in -əu, -ŋ, -ja, -l when they are borrowed to Raji. The grammatical borrowings are largely evidenced in the areas of morphology, and clause combining.